1997
DOI: 10.1074/jbc.272.24.15286
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the P1 Plasmid Partition Protein ParA by ATP, ADP, and P1 ParB

Abstract: ParA is an essential P1 plasmid partition protein. It represses transcription of the par genes (parA and parB) and is also required for a second, as yet undefined step in partition. ParA is a ParB-stimulated ATPase that binds to a specific DNA site in the par promoter region. ParA is an essential component of the P1 plasmid partition system (1). The prophage of bacteriophage P1 exists as an autonomously replicating plasmid, and its copy number is about the same as that of the bacterial chromosome (2). The P1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 25 publications
7
84
1
Order By: Relevance
“…S1). The significance of this small difference is not known, but similar values have been reported for ParA of P1 and SopA of F (12,31,32).…”
Section: Para2 Does Not Form Higher Molecular Weight Structures In Thesupporting
confidence: 62%
“…S1). The significance of this small difference is not known, but similar values have been reported for ParA of P1 and SopA of F (12,31,32).…”
Section: Para2 Does Not Form Higher Molecular Weight Structures In Thesupporting
confidence: 62%
“…Identification of putative 70 promoters was carried out using Targsearch (118). Putative Rho-independent transcriptional terminators were identified with the GCG program Terminator (40) and TIGR program TransTerm (85).…”
Section: Methodsmentioning
confidence: 99%
“…Regulatory regions of 38 operons contain one or more sequences that resemble strong 70 promoters (Table 4). Of 26 70 promoters identified previously by transcriptional fusion or primer extension experiments, only 9 had a match to the consensus sequence below 50% and required relaxing the stringency of the prediction program for their detection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The few detailed mutational studies of partition protein interactions concerned mainly type Ia systems (Walkertype ATPases with a DNA-binding function and ParB-like proteins with HTH DNA-binding motifs). ParB of Ia stimulates both the ATPase activity of ParA (Davey & Funnell, 1997) and the polymerization of ParA-like proteins Bouet et al, 2007;Machó n et al, 2007) crucial for separation of plasmid molecules. In the systems studied, it has been demonstrated that both proteins are able to interact with each other only in the dimeric form (Bouet & Funnell, 1999).…”
Section: Introductionmentioning
confidence: 99%